(3cJGH GdeHOC hGdeYGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdhGJg Ydi NjQ Ndbg eMeO hGdg GLeYjf hHYO aEfi GQjO Gf GOd ai gPg GdebGdI Ydi MbjbI YfO GdeTGFjf GdeMUdjf ef MGd GdeHOC hGdeYGO s
(3BNQgG (B:s
(3bGd Gddg JYGdi hCfRdfG ef GdSeGA eGA WghQG dfMi Hg HdOI ejJG eeG NdbfGg CfYGekG hCfGS hGdMeO dhGgH GdYbd JeJ GdQSGdI GdYQTjI s
(3HgG fXGe GdJYbjHIs
(3GdcJGH YHGQI Yf KdGK ebGdGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1456s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs